PENGUATAN PENDANAAN APBD BERBASIS INSTRUMEN FISKAL SYARIAH - Setianingrum, Any (Journal of Innovation in Business and Economics, 2015)
This study aims to determine the role of fiscal policy islam. The method used in this study is the case study method. Points Regional Government research Bekasi, Mechanical Sampling by interviewing respondents, obser-vation by observation by following some musrenbang socialization and discussion group forums in section / unit related work, the deepening of the documents related to local government financial policy. The results of this study indicate Kota Bekasi local government finance in systems and procedures, financial pattern has been going well, but the year 2012 -2014 budget funds can only cover approximately 30-50% of development proposals are inventoried in the deliberations development plan (musren-bang), so there many development proposals that can not be funded by the budget or in other words are still around 70-50% which can not be imple-mented.Keywords: Fiscal Policy, Islam, Local Government